Biosynthesis of rare 20(R)-protopanaxadiol/protopanaxatriol type ginsenosides through Escherichia coli engineered with uridine diphosphate glycosyltransferase genes - Yu, Lu (J Ginseng Res, 2019)
BACKGROUND: Ginsenosides are known as the principal pharmacological active constituents in Panax medicinal plants such as Asian ginseng, American ginseng, and Notoginseng. Some ginsenosides, especially the 20(R) isomers, are found in trace amounts in natural sources and are difficult to chemically synthesize. The present study provides an approach to produce such trace ginsenosides applying biotransformation through Escherichia coli modified with relevant genes. METHODS: Seven uridine diphosphate glycosyltransferase (UGT) genes originating from Panax notoginseng, Medicago sativa, and Bacillus subtilis were synthesized or cloned and constructed into pETM6, an ePathBrick vector, which were then introduced into E. coli BL21star (DE3) separately. 20(R)-Protopanaxadiol (PPD), 20(R)-protopanaxatriol (PPT), and 20(R)-type ginsenosides were used as substrates for biotransformation with recombinant E. coli modified with those UGT genes. RESULTS: E. coli engineered with GT95(syn) selectively transfers a glucose moiety to the C20 hydroxyl of 20(R)-PPD and 20(R)-PPT to produce 20(R)-CK and 20(R)-F1, respectively. GTK1- and GTC1-modified E. coli glycosylated the C3—OH of 20(R)-PPD to form 20(R)-Rh2. Moreover, E. coli containing p2GT95(syn)K1, a recreated two-step glycosylation pathway via the ePathBrich, implemented the successive glycosylation at C20—OH and C3—OH of 20(R)-PPD and yielded 20(R)-F2 in the biotransformation broth. CONCLUSION: This study demonstrates that rare 20(R)-ginsenosides can be produced through E. coli engineered with UTG genes.